Elevated Soluble PD-L1 in Pregnant Women's Serum Suppresses the Immune Reaction - Okuyama, Mai; Mezawa, Hidetoshi; Kawai, Toshinao; Urashima, Mitsuyoshi (Frontiers in Immunology, 2019)
Background Programmed death-ligand 1 (PD-L1) is expressed not only on some cancer cells, but also on the outer surface of placental syncytiotrophoblasts, which is assumed to induce maternal immune tolerance to fetal tissue via programmed death-1 (PD-1) receptors on T cells. Recently, levels of soluble forms of PD-L1 (sPD-L1) were reported to be higher in the serum of pregnant women (PW) than in non-pregnant women (non-PW). However, there have been no reports of the functional significance of PW’s serum containing high sPD-L1 levels. Therefore, the aim of the present study was to clarify the role of sPD-L1 in the sera of PW as an immunosuppressive molecule by in vitro assays. Methods As a post hoc analysis of our previous cohort study, 330 pairs of serum from PW during the third trimester and cord blood (CB) from paired offspring without major complications were examined. Serum levels of sPD-L1 and sPD-1 were measured by ELISA. On mixed lymphocyte culture (MLC), 3H-thymidine uptakes in the presence of PW’s, offspring’s, or non-PW’s serum were compared. Peripheral blood mononuclear cells (PBMCs) were cultured in the presence of PW’s serum stimulated with PHA, and then cytokine levels were measured in supernatants by multiple cytokine analysis with or without anti-PD-L1blocking antibody. Results The median sPD-L1 level was 8.3-fold and 6.9-fold higher in PW than in offspring and non-PW, respectively, whereas sPD-1 levels were lower in PW and offspring than in non-PW. On MLC, 3H-thymidine uptake in the presence of autoantigen was strongly reduced by co-culture with serum of both PW and offspring, compared with serum of non-PW. In contrast, uptake in the presence of alloantigen was moderately inhibited by PW’s serum, whereas it was less suppressed by offspring’s serum, compared with non-PW’s serum. In the culture of PBMCs, tumor necrosis factor-α, interferon gamma, interleukin (IL)-2, and IL-4 levels were significantly higher in the presence of anti-PD-L1 blocking antibody than in culture not treated with antibody (all P<0.05) or culture treated with isotype control antibody (all P<0.05). Conclusion The levels of sPD-L1 are elevated in PW’s serum, which may, at least in part, suppress maternal immunity.